(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
This article examines key changes that occur during adolescence, including shifts in emotional regulation, identity formation, peer relationships, and mental health. Results indicate significant changes in emotional reactivity, self-esteem, and coping strategies. Moreover, the study highlights how peer influence and social networks impact the mental health of teenage boys, leading to an increased risk of anxiety and depression.